Pendidikan Islam Dalam Perspektif Al-Ghazali - Azahra, Fatma (Indonesian Research Journal on Education, 2023)
The purpose of this article is to analyze the conception of Islamic Education from Al-Ghazali's perfection. This article uses library research to review that Al-Ghazali has a deep understanding of Islamic Education. This paper also reveals his thoughts and understanding of education management, managing students, and managing curriculum. This paper concludes that Education according to Al-Ghazali is the process of humanizing humans until the end of their lives towards approaching themselves to God so thatthey become perfect human beings. Al-Ghazali explained the things that must be met by students in the learning process: learning is a process of the soul, requires concentration, and must be based on humility. Regarding a curriculum, he pays special attention to the science of religion and ethics and is based on two tendencies: religious and tasawuf tendencies; and pragmatic tendencies. According to him, the meaning and purpose of Islamic education is education that seeks and aims at forming a complete human being. Meanwhile, in making a curriculum Al-Ghazali has two tendencies, namely the tendencytoward religion and the pragmatic tendency. As for the material aspects of Islamic education, according to Al-Ghazali thought, includes education in the faith, morals, reason, social and jurisprudence. According to him, a good teacher besides being intelligent and perfect in mind also has commendable qualities.